Soft landing and inflation scares - James B. Bullard; Alex Grimaud; Isabelle Salle; Gauthier Vermandel (Tinbergen Institute, 2025)
We discuss the timing and strength of the Fed's reaction to the recent inflation surge within an estimated macroeconomic model where long-run inflation expectations are heterogeneous and can lose their anchoring to the target. The resulting inflation scare worsens the real cost of disinflation. We derive a closed-form solution that retains the entire time-varying cross-sectional distribution of subjective inflation beliefs. We estimate the model using Bayesian techniques on both US macroeconomic time series and forecast data from the Survey of Professional Forecasters. Counterfactual simulations show that the timing - rather than the strength - of the policy reaction to the inflation surge is critical to contain the development of an inflation scare and prevent the entrenchment of above-target inflation. We show that the Fed fell behind the curve in 2021 since an earlier tightening could have reduced the inflation peak without triggering a recession. However, further delays would have unanchored inflation expectations, aggravated the inflation scare and strengthened the inflation surge, resulting in larger output losses.
Keywords: C63; E31; E52; E70; 330; Monetary Policy; Inflation scare; Heterogeneous expectations; Bayesian estimation